Integrating islamic values into trauma healing: a spiritual-based counseling approach among muslim trauma survivors - Silawati Silawati; Anisa Putri (Asian Journal of Islamic Studies and Society, 2024)
Trauma places a heavy psychological burden on Muslim communities in Indonesia, particularly in Riau Province, where socioeconomic difficulties, marital breakdown, occupational adversities, and personal loss converge to produce profound suffering. While spirituality is increasingly recognized as a meaningful resource for healing, existing literature offers limited empirical insight into how Indonesian Muslim trauma survivors actually draw on Islamic values in their recovery. This qualitative phenomenological study explored the lived experiences of Muslim trauma survivors across three sites in Riau  Pekanbaru, Kampar, and Siak  examining how Islamic spiritual practices function as a framework for counseling and healing. Using purposive sampling, twelve primary informants were selected from an estimated population of two hundred Muslim trauma survivors; two Islamic counselors and one religious scholar were added for source triangulation. Data were gathered through in-depth interviews, participant observation, and documentary analysis, and analyzed thematically following Miles and Huberman's interactive model. Four major themes emerged: (1) the phenomenology of trauma within an Islamic life context; (2) Islamic spiritual practices as active healing mechanisms; (3) Islamic counseling as a structured therapeutic pathway; and (4) spiritual resilience and posttraumatic growth. Practices including dhikr, tahajjud prayer, Qur'anic recitation, ruqyah, and participation in pengajian circles proved to be psychologically meaningful healing interventions rather than mere ritual observance. The integration of tawakal, sabar, and tawbah within counseling settings further strengthened survivors' psychological resilience. This study offers a contextually grounded framework for Islamic spiritual counseling, with practical implications for Muslim mental health practitioners, counselors, and policymakers in majority-Muslim regions.